CD19 chimeric antigen receptor T cell therapy for haematological malignancies. (5th March 2015) - Ghorashian, Sara; Pule, Martin; Amrolia, Persis
Summary: T cells can be redirected to recognize tumour antigens by genetic modification to express a chimeric antigen receptor (CAR). These consist of antibody‐derived antigen‐binding regions linked to T cell signalling elements. CD19 is an ideal target because it is expressed on most B cell malignancies as well as normal B cells but not on other cell types, restricting any 'on target, off tumour' toxicity to B cell depletion. Recent clinical studies involving CD19 CAR‐directed T cells have shown unprecedented responses in a range of B cell malignancies, even in patients with chemorefractory relapse. Durable responses have been achieved, although the persistence of modified T cells may be limited. This therapy is not without toxicity, however. Cytokine release syndrome and neurotoxicity appear to be frequent but are treatable and reversible. CAR T cell therapy holds the promise of a tailored cellular therapy, which can form memory and be adapted to the tumour microenvironment. This review will provide a perspective on the currently available data, as well as on future developments in the field.